Effects of Habitat Fragmentation on Carabid Beetles: Experimental Evidence - Davies, Kendi F.; Margules, Chris R. (The Journal of animal ecology, 1998)
1. We tested for effects of habitat fragmentation in a controlled, replicated, field experiment, in south-eastern Australia. Our experimental subjects were eight carabid beetle species, and the carabid assemblage (45 species). Monitoring was by pitfall trapping in forest remnants and in adjacent continuous-forest controls. Remnants were of three sizes (0.25, 0.875, 3.062 ha.). Monitoring commenced 2 years prior to habitat fragmentation. Here we present results for 6 years after habitat fragmentation (4 years for species richness). 2. We tested four hypotheses. Hypothesis one: habitat fragmentation reduces species richness in the remaining remnants. Carabid species richness was not different in habitat remnants compared to continuous forest, neither was carabid richness different for remnants of different sizes, or at monitoring sites close to remnant edges compared to sites in remnant interiors. 3. Hypothesis two: populations decline as a result of habitat fragmentation. Two species of eight were completely isolated on remnants and both declined in abundance on remnants compared to control plots in continuous forest. The other six species responded in various ways, which included relative increases and decreases in abundance and no change, but as they were not completely isolated on remnants, their responses could not be explained by isolation. 4. Hypothesis three: remaining subpopulations decline further on smaller habitat remnants than on larger remnants. Three species responded to remnant size; one was most abundant in small remnants, the second was most abundant in large remnants, and the third was equally abundant in small and large remnants and less abundant in medium-sized remnants. 5. Hypothesis four: populations near to remnant edges decline further than populations in remnant interiors. Two species were more likely to occur in remnant interiors than at edges, whereas three species were equally likely to occur in remnant interiors and at edges. 6. The effects of habitat fragmentation may be the consequence of: (i) isolation; and (ii) habitat modification. In this study, we were able to consider effects of isolation for two carabid species. We tested only one aspect of the habitat modification hypothesis, edge effects. We discuss the possibility that other aspects of habitat modification in remnants may explain some of our results and suggest that this is where future research be directed.